First patient in Serbia with biochemically and genetically diagnosed pyridoxine-dependent epilepsy - Ješić, Miloš M; Ješić, Maja D; Buljugić, Svetlana; Živanović, Aleksandra (Vojnosanitetski pregled, 2017)
Introduction. Pyridoxine-dependent epilepsy (PDE) is a rare autosomal recessive inborn error of metabolism present with early-onset seizures resistant to common anticonvulsants. PDE has been shown to be caused by a defect of a α-aminoadipic semialdehyde dehydrogenase (also known as ALDH7A1 or antiquitin) in the cerebral lysine degradation pathway. Its deficiency results in accumulation of α-aminoadipic semialdehyde (α-AASA), piperideine -6-carboxylate and pipecolic acid, which serve as diagnostic markers in urine, plasma and cerebrospinal fluid of the disease. α-Aminoadipic semialdehyde dehydrogenase is encoded by the ALDH7A1 or antiquitin gene and definite confirmation of diagnosis of PDE is made by genetic analysis. Case report. We present a first patient in Serbia who was diagnosed clinically, biochemically and genetically. We suspected PDE due to drug-resistant seizures in the seventh day of life when we attempted with pyridoxine. Since that time the patient has taken pyridoxine and the seizures have not recured. Our patient had markedly elevated α-AASA in urine while on treatment with individual dosages of pyridoxine. Molecular-genetical analysis identified mutations of the ALDH7A1 (antiquitin) gene. Conclusion. α-AASA is reliable marker to select PDF patient for molecular analysis of the ALDH7A1(antiquitin) gene. Diagnosis is confirmed by molecular-genetical analysis and pyridoxine withdrawal is no longer needed to establish the diagnosis of „definite“ PDE.
Keywords: epilepsy; infant; newborn; vitamin B6; genetic diseases; inborn; diagnosis; differential; drug therapy; serbia